Platelet Aggregation in Intracranial Stents May Mimic In-Stent Restenosis - Mazighi, M. (AJNR Am J Neuroradiol, 2010)
We report the case of an early ISR that was due to platelet aggregation despite correct observance of a standard antiplatelet regimen. Biologic testing showed clopidogrel inefficiency, and ISR disappeared on angiography after a loading dose of clopidogrel. This result suggested that the arterial lumen reduction was due to platelet aggregation rather than in-stent myointimal hyperplasia. This observation emphasizes the importance of verifying the efficacy of clopidogrel before placing a stent.